Baseline study for impact assessment of high quality insect resistant cowpea in West Africa - Coulibaly, O.; Aitchedji, C.C.; Gbegbelegbe, Sika; Mignouna, H.; Lowenberg-Deboer, J. (2008)
Cowpea is the most important grain legume and fodder crop in the dry savannas of Africa. Grown on more than 12.5 million hectares, grain yields from improved varieties are higher than local varieties, but require 2 to 3 insecticide sprays to control major pests compared to local varieties. Losses due to Maruca alone reach 80% and so far resistance to Maruca has been limited. To address some of these challenges the African Agricultural Technology Foundation (AATF) has initiated a project which promotes farmers access to improved cowpea technologies and biotechnological products. Availability of Bt cowpea lines with resistance to Maruca will contribute significantly to: (1) increased production and incomes, (2) improved nutrition, (3) enhanced soil fertility, (4) increased storability, and (5) decreased pesticide use.The study initiated by AATF and executed by the International Institute of Tropical Agriculture (IITA) and Purdue University aims to:1. elicit consumer preferences, acceptability, willingness to pay and adaptability of Bt cowpea to local conditions in west Africa 2. assess the competitiveness and potential market niches for Bt cowpea3. identify strategies for capacity building of west African seed organisations for Bt cowpea 4. assess the ex-ante economic impact of Bt cowpea at farm, country and region levels.Preliminary results show that: 1. information exchange and awareness are important for the adoption and large diffusion of Bt cowpea2. there is a high willingness to pay for Bt cowpea seed by farmers 3. given the potential of reducing health hazards by lowering the use of toxic synthetic pesticides, both farmers and consumers are willing to pay a premium price for Bt cowpea as an alternative to harmful cotton pesticides. The opportunity costs of using cotton insecticides include the economic losses encountered by the farm household when a family member is sick due to the misuse of chemical insecticides4. urban consumers in regional markets believe that Bt cowpea may be safer than conventional cowpea treated with chemicals5. Bt cowpea will raise incomes substantially at farm, household, community and regional levels.